2007
DOI: 10.1177/146499340700700303
|View full text |Cite
|
Sign up to set email alerts
|

Economic reform and foreign direct investment in Latin America

Abstract: After almost 25 years of experimenting with the neo-liberal economic reforms collectively known as 'Washington Consensus' policies, Latin Americans are starting to re-assess the merits of these policies at the voting booth. Whereas one of the key policies of the 'Washington Consensus' package was the liberalization of investment regimes, many of the newly elected governments are beginning to scrutinize the role of foreign direct investment (FDI) in their countries. Indeed, some nations have gone as far as to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Those that focus on Latin America identify several determinants of the flow of FDI to this region, including market size and growth, level of trade openness, human capital (education level), tax liberalization, and economic and political stability of the host country (although the latter factor reveals a certain ambiguity about the expected ef fect). As reported by Porzecanski and Gallagher (2007), there is unanimity among empirical studies on FDI in Latin America that the key determinants of FDI in the region are the (large) size and growth of the market, and a (low) level of inflation and debt (that is, macroeconomic stability). In this paper, our aim is to improve our knowledge about FDI in Latin America using cluster analysis, a technique rarely used in studies on this topic.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…Those that focus on Latin America identify several determinants of the flow of FDI to this region, including market size and growth, level of trade openness, human capital (education level), tax liberalization, and economic and political stability of the host country (although the latter factor reveals a certain ambiguity about the expected ef fect). As reported by Porzecanski and Gallagher (2007), there is unanimity among empirical studies on FDI in Latin America that the key determinants of FDI in the region are the (large) size and growth of the market, and a (low) level of inflation and debt (that is, macroeconomic stability). In this paper, our aim is to improve our knowledge about FDI in Latin America using cluster analysis, a technique rarely used in studies on this topic.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…Conversely, the non-populist's sample overall goodness of fit is half, and the relatively weak and positive direction of the main independent variable suggests that increasing the ratio of FDI to GDP is somehow related to increasing inflation rates. One argument used to explain this phenomenon is that FDI streams in Latin America have not delivered the promised spillovers in terms of technological transfer and learning, and have not generated the theoretical forward and backward linkages to the host economy (Porzecanski and Gallagher, 2007).…”
Section: Statistical Tests and Resultsmentioning
confidence: 99%
“…Second, FIEs are also interested in investing in emerging markets to maximise their sales. For example, Porzecanski and Gallagher (2007) found that 80 per cent of the FDI in South America have been concentrated in Brazil, Mexico, Argentina, Chile and Venezuela, and were mostly designed to target domestic markets. Third, economic agglomeration has become an important factor for FIEs' location decisions in China (Tuan & Ng 2004).…”
Section: Research Background and Conceptual Frameworkmentioning
confidence: 99%